Analisis Gaya Kepemimpinan, Komitmen, dan Kedisiplinan Terhadap Peningkatan Motivasi Kerja Pegawai Kantor Kec. Tegalsari Surabaya - Iwang Suwaningsih (Jurnal Bisnis dan Keuangan, 2016)
This study aims to determine the effect of Leadership Commitment and Disciplinesignificant effect partially and simultaneously to Increase Employee Work MotivationTegalsari Surabaya District Office. This study uses survey research approachEksplanaratif by enforcing data via the primary data of the data relating to the variablescollected from respondents using questionnaires. This type of research, including researchkoresional who want to see the relevance of independent variables with the dependentvariable. The population is Tegalsari Surabaya District Office Employees. This study wasconducted involving 30 respondents and using multiple linear regression analysis. Theregression equation is: Y = 3.441 + 0.266 + 0.104 X1 + 0.132 X2 X3. From this researchit was discovered and drawn the following conclusions: (1) Leadership, Commitmentand Discipline significant effect partially to Increase Motivation Employee Work DistrictOffice Tegalsari Surabaya, (2) leadership, commitment and discipline significant effectsimultaneously to Increase Motivation Employee Work Office Tegalsari District ofSurabaya, (3) Leadership dominant influence significantly the Employee Work MotivationImprovement District Office Tegalsari Surabaya.